LEGAL VALIDITY FOR NAZHIR AS A MANAGER OF WAKAF ASSET IN TAKING BACK WAKAF ASSETS THAT ARE NOT USED IN ACCORDANCE WITH THEIR DESIGNATION - Natigor Daulay, R. Fahmi (NOMOI Law Review, 2025)
This study examines the legal validity for Nazhir as a waqf asset manager in reclaiming waqf assets that are not used according to their intended use. The research method used is normative juridical. The results of the study indicate that the validity of Nazhir in the withdrawal of misused waqf assets is analyzed based on Decision No. 22/Pdt.G/2017/MS-Aceh which is in line with the provisions of Article 42 of Law of the Republic of Indonesia Number 41 of 2004 concerning Waqf, waqf assets that were initially loaned by Nazhir can be withdrawn if proven to be misused. The judge's consideration in granting the withdrawal of misused waqf assets in Decision No. 22/Pdt.G/2017/MS-Aceh is based on the fact that legally there is no legal reason for the Defendants/Appellees to illegally and unlawfully detain and control the disputed object as the legal property of YPI Bireuen.